2003
DOI: 10.1190/1.1543202
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface seismic reflection profiling of the Matanuska Glacier, Alaska

Abstract: Several common‐midpoint seismic reflection profiles collected on the Matanuska Glacier, Alaska, clearly demonstrate the feasibility of collecting high‐quality, high‐resolution near‐surface reflection data on a temperate glacier. The results indicate that high‐resolution seismic reflection can be used to accurately determine the thickness and horizontal distribution of debris‐rich ice at the base of the glacier. The basal ice thickens about 30% over a 300‐m distance as the glacier flows out of an overdeepening.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…A radar survey also documented the thickening of the basal ice with distance up the adverse slope of an overdeepening behind the glacier terminus (Baker et al . ).…”
Section: Field Site and Sampling Of The Diamictonmentioning
confidence: 97%
See 1 more Smart Citation
“…A radar survey also documented the thickening of the basal ice with distance up the adverse slope of an overdeepening behind the glacier terminus (Baker et al . ).…”
Section: Field Site and Sampling Of The Diamictonmentioning
confidence: 97%
“…A systematic ground‐penetrating radar survey near the cut bank has shown that the basal ice extends in the subsurface towards the glacier and into the moraine complex, and that the diamicton can be traced as a distinct horizon on the buried ice surface (Baker et al . ,b; Larson et al . : fig.…”
Section: Field Site and Sampling Of The Diamictonmentioning
confidence: 99%
“…They have an average relief of 1-3 m and are commonly flanked by shallow closed depressions b 1 m deep. Recent geophysical studies have shown some of the hummocks to be ice cored (Baker et al, 2003a;Larson et al, 2003) and that some of the irregular terrain can be attributed to glaciotectonic deformation of stacked remnants of buried debris-laden ice (Baker et al, 2003b).…”
Section: Hummocky Terrainmentioning
confidence: 97%
“…They are separated by linear depressions N1 m deep and generally have steep proximal and distal slopes. At least some of the ridges are ice cored (Baker et al, 2003a;. The debris fans occur mainly on the flanks of the ridges but some extend through ridge gaps and into linear depressions between ridges.…”
Section: Hummocky Terrainmentioning
confidence: 98%
“…Comparison of the isolated EIRs with cross‐borehole seismic and GPR data reveals that strong electrokinetic conversions occur within the surface snow pack, near the interface between dry and wet ice, and at the ice‐bed interface. Baker et al [2003] observed high‐frequency seismic reflections from the ice‐bed interface at depths of >100 m at Matanuska glacier, Alaska, generated by a hammer‐and‐plate source. Observation of EIRs from the ice‐bed interface (Figure 5), albeit weak compared to snow and dry‐wet ice interface EIRs, therefore does not appear unrealistic.…”
Section: Synthesis and Discussionmentioning
confidence: 98%